2021
DOI: 10.3390/app11209529
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bond Formation between Vertically Aligned Carbon Nanotubes and Metal Substrates at Low Temperatures

Abstract: The exceptional physical properties of carbon nanotubes (CNTs) have the potential to transform materials science and various industrial applications. However, to exploit their unique properties in carbon-based electronics, CNTs regularly need to be chemically interfaced with metals. Although CNTs can be directly synthesized on metal substrates, this process typically requires temperatures above 350 °C, which is not compatible for many applications. Additionally, the CNTs employed here were highly densified, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 82 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…Carboxyl-functionalized CNT film and amine-functionalized Au surface were clamped to promote chemical bonding between CNT and Au (to form Au-L-CNT). A detailed description of the process is described in our previous work . The schematics of electrode fabrication are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carboxyl-functionalized CNT film and amine-functionalized Au surface were clamped to promote chemical bonding between CNT and Au (to form Au-L-CNT). A detailed description of the process is described in our previous work . The schematics of electrode fabrication are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…To take advantage of the physical properties of aligned CNT even further, a covalent attachment to a metal substrate can be used. Grafting of the Au surface by diazonium salts with covalent Au–C bond formation has been previously shown. The introduction of aryl group linkers allows for the further surface functionalization with CNT . Such a modification can provide additional mechanical robustness and create directed efficient electron transport pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, the cost of and potential damage caused by such high-temperature treatments make the use of linker molecules to chemically bond CNTs to metal surfaces at reasonably lower temperatures a more promising approach for practical applications. 22 Linker molecules as bridging agents may also aid in overcoming the energy mismatch between CNTs and metals, thus providing a low-cost method for forming chemical bonds between CNTs and metals under mild conditions. Theoretical studies have shown that CNT−linker−metal structures provide better interface conductivity than mere physical metal−CNT interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, induction heating of a Au–CNT interface can reduce the contact electrical resistance by up to 99% . However, the cost of and potential damage caused by such high-temperature treatments make the use of linker molecules to chemically bond CNTs to metal surfaces at reasonably lower temperatures a more promising approach for practical applications . Linker molecules as bridging agents may also aid in overcoming the energy mismatch between CNTs and metals, thus providing a low-cost method for forming chemical bonds between CNTs and metals under mild conditions.…”
Section: Introductionmentioning
confidence: 99%